Union Territory of Pondicherry Draft Annual Plan 1986-87 Seventh Five Year Plan 1985-90 Scheme-Wise Details - Planning Commission (Planning Commission, 1986)
The Territory constitutes a single revenue district consisting of 292 census villages, 129 revenue villages, 4 sub-Taluks and 2 taluks. For the purpose of development administration the Territory is divided into 3 and 5/6 blocks consisting of 47 circles of village level workers. Pondicherry Panchayats Act of 1973 and Municipalities Act of 1973 came into force in 1974. There are A Municipalities, namely, Pondicherry, ;:Karaikal,. Mahe and Yanam. There are 11 Commune Panchayatsy 6 in Pondicherry region, namely, Ozhukarai, Villianur, Mannadipet, Ariankuppam, Bahour, Nettapakkam and 5 in Karaikal region, namely, Thirunallar, Neravy, Nedungadu Kottucherry and T.R. Pattinam.
Scheme-Wise Details
Government of Pondicherry